Transport‐based equivalent circuit for semiconductor nanoparticle in terahertz frequency range. Issue 1 (1st January 2013) - Shen, T.; Hu, Z.; Wong, T.
Abstract : By consideration of the physical process of charge carrier motion and lattice polarisation, an equivalent circuit for a semiconductor nano‐particle in the terahertz frequency range is obtained. All circuit elements are of electrical nature and can be directly expressed in terms of material parameters. When the generalised admittance of the circuit is multiplied by the intensity of an externally applied field, the total induced dipole moment of the nanoparticle results, which is in good match to that given by field analysis and simulation. The readily obtained polarisability can serve as the basis of analysis for composite structures and aggregates of which the nanoparticle is a constituent.